2015
DOI: 10.1055/s-0035-1549100
|View full text |Cite
|
Sign up to set email alerts
|

Acute Colonic Pseudoobstruction

Abstract: Acute colonic pseudoobstruction (ACPO), often referred to as Ogilvie syndrome, is a clinical entity characterized by severe colonic distension (adult acute megacolon) in the absence of mechanical obstruction. It can result in abdominal ischemia and perforation if left untreated. This article discusses the epidemiology and current pathophysiologic theories of ACPO as well as the clinical presentation and diagnostic modalities utilized to identify the disease. In addition, this article describes the current trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 30 publications
0
38
0
5
Order By: Relevance
“…For that reason, it becomes important to identify patients that may be at risk of dying during their ICU stay. Out dataset revealed that the majority of admitted patients are elderly individuals with a median age of 63 years [34][35][36]. In this cohort of patients, we observed labs which were performed in the first 24 hours to predict overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, it becomes important to identify patients that may be at risk of dying during their ICU stay. Out dataset revealed that the majority of admitted patients are elderly individuals with a median age of 63 years [34][35][36]. In this cohort of patients, we observed labs which were performed in the first 24 hours to predict overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Significant abdominal distention with tympany is invariably seen on physical examination. Auscultation often reveals high-pitched but sometimes tinkling bowel sounds (Chudzinski et al 2015). However, bowel sounds may be absent in 10% of cases (Vanek and Al-Salti 1986).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…The decision must be made on a case by case basis. The only objective elements that guide the gastroenterologist are the diameter of the cecum (greater than 12 cm) and the duration of the pseudo-obstruction (more than 6 days) 11 .…”
Section: ) Exsufflation Of the Colonmentioning
confidence: 99%